A NEW FOSSIL CLARIFIES THE ANATOMY AND PHYLOGENETIC RELATIONSHIPS OF THE EOCENE GYMNODONT FISH †ZIGNOICHTHYS OBLONGUS (ZIGNO, 1874) - LORENZO RIDOLFI; GIUSEPPE MARRAMÀ; JAMES TYLER; Giorgio Carnevale (Rivista Italiana di Paleontologia e Stratigrafia)
The Eocene tetraodontiform fish †Zignoichthys oblongus (Zigno, 1874) from the Bolca Konservat-Lagerstätte, northeastern Italy, is redescribed in detail based upon new material. This taxon exhibits a combination of features (parasphenoid shaft-like and bearing a ventral flange; non-protractile upper jaw; teeth incorporated into beak-like jaws; premaxilla without ascending process; palatine massive and firmly connected to the ethmo-vomerine region; supracleithrum distinctly oblique) that clearly supports its assignment to the gymnodonts, suborder Tetraodontoidei. The analysis of this new material also demonstrates that the previous apparent absence of plesiomorphic characters (e.g., spiny dorsal fin) was the result of taphonomic biases. †Zignoichthys shares a number of features (basisphenoid, urohyal, beryciform foramen perforating the anterior ceratohyal, ribs, more than 20 vertebrae, epineurals, 12 principal caudal-fin rays, procurrent caudal-fin rays, unfused hypurals, autogenous haemal arch and spine of the third preural vertebra, dorsal-fin spines, scapular foramen entirely enclosed by the scapula) with the extant Triodon, which support their sister-group relationship and their basal position within the Tetraodontoidei. An analysis of the skeletal morphology of †Zignoichthys is presented and compared with that of other gymnodonts. We also compare our phylogenetic results with previous hypotheses about Tetraodontoidei relationships.